The Formation of Al-Si Aluminide Coatings by Pack Cementation Method on TNM-B1 Intermetallic Alloy - Woźniak, Mateusz; Góral, Marek; Kościelniak, Barbara (Advances in Mechanical and Materials Engineering, 2023)
The TiAl intermetallics are the promising material for aerospace application. According to its insufficient oxidation resistance above 900oC the using of protective coatings is necessary. The diffusion aluminide coatings based on TiAl2 or TiAl3 phases permits to formation of alumina scale on the surface of TiAl alloys. The pack cementation with Si doping is one of the most popular method of this type of coatings production. In present article the influence of Si content in the pack, process time and temperature during pack cementation process were investigated. The thickness of obtained coating was in range 20-50 μm. When Si content was higher the formation of titanium silicides was observed using almost all analysed values of process parameters. The results showed that using of 24 wt. % Si containing pack and process parameters: 4h/950oC enables to obtain the coating characterized by optimal thickness and structure. The porosity and cracks in coatings according to TiAl phases brittleness was observed.